The Use of Memes and Satire by the Alt-right and Gen Z Activists – Exclusion vs Inclusion - Viveca S. Greene (The Journal of Intelligence, Conflict and Warfare, 2021)
On November 27, 2020, Viveca S. Greene presented The Use of Memes and Satire by the Alt-right and Gen Z Activists – Exclusion vs Inclusion at the 2020 CASIS West Coast Security Conference. The presentation was followed by a group panel for questions and answers. Main discussion topics included humour studies, the Alt-Right, satire, and memes.